2021
DOI: 10.3390/e23080979
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and Rheological Properties of Graphene Nanopowders Nanofluids

Abstract: The dynamic viscosity and rheological properties of two different non-aqueous graphene nano-plates-based nanofluids are experimentally investigated in this paper, focusing on the effects of solid volume fraction and shear rate. For each nanofluid, four solid volume fractions have been considered ranging from 0.1% to 1%. The rheological characterization of the suspensions was performed at 20 ∘C, with shear rates ranging from 10−1s−1 to 103s−1, using a cone-plate rheometer. The Carreau–Yasuda model has been succ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 63 publications
4
10
2
Order By: Relevance
“…After fitting the data of viscosity with volume fractions using the model (5), for different shear rates. In the case of EG, the model applied well to the description of the evolution of EG viscosity as a function of GNP volume fraction φ and a quasi-systematic increase in the dynamic viscosity with the GNP volume fraction has been observed, whatever the shear rate considered, which is same observed in the study of Bakak et al [3]. For GL, the results of fitting the Vallejo model are in good agreement with the data.…”
Section: Effect Of Solid Volume Fraction On Viscositysupporting
confidence: 82%
See 3 more Smart Citations
“…After fitting the data of viscosity with volume fractions using the model (5), for different shear rates. In the case of EG, the model applied well to the description of the evolution of EG viscosity as a function of GNP volume fraction φ and a quasi-systematic increase in the dynamic viscosity with the GNP volume fraction has been observed, whatever the shear rate considered, which is same observed in the study of Bakak et al [3]. For GL, the results of fitting the Vallejo model are in good agreement with the data.…”
Section: Effect Of Solid Volume Fraction On Viscositysupporting
confidence: 82%
“…In Fig. 7, it can be observed that the viscosity of EG+GNP8 nanofluids also decreases at higher temperatures and similar trends have also been observed before [3,5]. There is an evident increase of viscosity at high concentrations, e.g.…”
Section: Viscosity Trendssupporting
confidence: 78%
See 2 more Smart Citations
“…Therefore, finding a more effective lubricant for OA patients may be of great significance for the improvement of their joint function ( Lin and Klein, 2021 ). The lubricant suspension added with NPs is called nano-lubricant, and NPs can be stably suspended in the lubricant to enhance the lubrication effect of the lubricant ( Bakak et al, 2021 ). Graphite nanoplatelets (GNP) can improve the lubricating property of the lubricant.…”
Section: Osteocartilage Regeneration Scaffoldmentioning
confidence: 99%